Answer:
w = 0 , -3 , 3
Step-by-step explanation:
w³ - 9w = 0
w(w² - 9) = 0
w(w² - 3²) = 0
w(w+3)(w-3) = 0 {a² - b² = (a + b)(a - b) }
w = 0 ; w + 3 = 0 ; w - 3 = 0
w = -3 ; w = 3
w = 0 , -3 , 3
Answer:
34:48
Step-by-step explanation:
adult:child
34:48
simplify: ÷2
17:24
Answer:
Step-by-step explanation:
24/9 would be 8:3
Hope this helps :)
Answer:
(x - 4)² - 11
Step-by-step explanation:
Given
x² - 8x + 5
To obtain the required form use the method of completing the square.
add/subtract ( half the coefficient of the x- term)² to x² - 8x
= x² + 2(- 4)x + 16 - 16 + 5
= (x - 4)² - 11